Management of patients with acute ST-segment elevation myocardial infarction in Russian hospitals adheres to international guidelines. Issue 1 (23rd January 2020) - Kontsevaya, Anna V; Bates, Katie; Schirmer, Henrik; Bobrova, Natalia; Leon, David; McKee, Martin
Abstract : Objective: Russia has one of the highest cardiovascular mortality rates. Modernisation of the Russian health system has been accompanied by a substantial increase in uptake of percutaneous coronary intervention (PCI), which substantially reduces the risk of mortality in patients with acute ST-elevation myocardial infarction (STEMI). This paper aims to describe contemporary Hospital treatment of acute STEMI among patients in a range of hospitals in the Russian Federation. Methods: This study used data from a prospective observational cohort of 1128 suspected patients with myocardial infarction recruited in both PCI and non-PCI hospitals across 13 regions and multiple levels of the health system in Russia. The primary objective was to examine the use of reperfusion strategies in patients with STEMI. Results: Among patients reaching PCI centres within 12 hours of symptom onset, the vast majority received angiography and PCI, regardless of age, sex and comorbidity, in line with current European Society of Cardiology guidelines. Conclusion: Patients reaching Russian hospitals are very likely to receive appropriate treatment, although performance varies. The best hospitals can serve as beacons of good practice as PCI facilities continue to expand across Russia where geography allows.